(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the impact of translation strategies on the student's thinking in the process of language learning. The study considers translation activity not only as a method of mastering language tools, but also as a cognitive process. Through translation, the student develops analytical and creative thinking, understanding the semantic, cultural and logical layers of language units. The article highlights the impact of instructional and independent translation strategies on the student's thinking style, level of language perception and communicative competence. According to the results of the analysis, the rational use of translation strategies forms interlinguistic thinking, intercultural understanding, and metacognitive skills in language learners. At the same time, the article also substantiates the effectiveness of the translation approach combined with modern pedagogical technologies in teaching a foreign language.